Pros and Cons of Online Criminal Case Settlement During the Covid-19 Pandemic: Study on Islamic Criminal Law - Hasan, Hamzah (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin Makassar, 2021)
The online criminal trial discourse has become a hot discussion topic by criminal law practitioners, especially regarding the obscenity case in Petamburan that involved the suspect, HRS. HRS himself and his lawyer refused to hold the online trial for being contrary to the Criminal Procedure Code (KUHAP) although there is a Memorandum of Understanding between the Supreme Court, Attorney General's Office, Police, and the Directorate General (Ditjen) of Corrections regarding the Implementation of Criminal Trial Proceedings via video conferencing as efforts to prevent the spread of Covid-19 on April 13, 2020. This study aims to provide an answer that Islamic criminal procedural law can accommodate models of virtual criminal case resolution because it considers emergency situations. Moreover, the reason for the emergency has to do with humanity. The data used as materials for data analysis was library research which were taken from fiqh books, written documents, laws and other regulations. The results show that Islamic criminal law can consider its feasibility.Keywords: Virtual criminal court – Islamic criminal